Ursolic Acid and Related Analogues: Triterpenoids with Broad Health Benefits - Huynh Nga Nguyen; Sarah L. Ullevig; John D. Short; Luxi Wang; Yong Joo Ahn; Reto Asmis (MDPI AG, 2021)
Ursolic acid (UA) is a well-studied natural pentacyclic triterpenoid found in herbs, fruit and a number of traditional Chinese medicinal plants. UA has a broad range of biological activities and numerous potential health benefits. In this review, we summarize the current data on the bioavailability and pharmacokinetics of UA and review the literature on the biological activities of UA and its closest analogues in the context of inflammation, metabolic diseases, including liver and kidney diseases, obesity and diabetes, cardiovascular diseases, cancer, and neurological disorders. We end with a brief overview of UA's main analogues with a special focus on a newly discovered naturally occurring analogue with intriguing biological properties and potential health benefits, 23-hydroxy ursolic acid.